Enhancing Students’ Reading Skills Through Google Doc as Alternative E-Learning for Essay Exercise at Senior High School 3 Jambi City - Rifdhal Hadista; Suyadi Suyadi; Siti Aisyah (Universitas Batanghari Jambi, 2021)
Reading is a result of interaction between writer’s mind and the reader’s mind. Which in this process the reader tries to create the meanings that intended by the writer. In addition, the readers have discovered by find out what readers main idea of their reading. The purpose of this research is finding out whether the google doc is effective for an English essay exercise to improve students English Reading skill as they doing e-learning through school from home program. The objective of this research to find out the effectivity students in enhancing their English writing by conducting an essay exercise digitally through the google doc as an alternative e-learning. The research design in this research is quantitative. The research conducted Senior High School 3 Jambi City. The population of this research is eleventh grade of science IV class students. The data obtained through quantitative research with the test. Overall, after the google doc was implemented in the test, the result of the test is quite good, in the test result, all of each entire students dominates the entire middle score categorize which the average score is from 70. Moreover, the mean score results from the entire of all students score result is 68.8 which is means that the mean score is in good criteria category. In addition, it can be concluded that there is a significance change of students English Reading before and after implementing google doc as English essay exercise.Key Words: Reading Skill, E-learning, Essay Exercise, Google Doc.